Moderating effect of knowledge on the relationship between valence framing of covid-19 online news and preventive behaviours - Joseph, Joanneia Selin (2022)
Corona, a newly discovered virus was declared pandemic and considered a global threat to human-being. When it comes to seeking information, the role of media cannot be underestimated because people’s need for information increase especially during pandemic and global-health crisis. The way media frame news may influence public’s preventive behaviours differently in terms of positive (gain) and negative (loss) framing. This scenario is known as valence framing. Past studies have shown that gain frame enhance preventive behaviours better than loss frame. This research attempts to clarify the valence frame effects of COVID-19 online news towards preventive behaviours while determining the moderating role of knowledge in the relationship. Using a selfadministered questionnaire, 150 participants of both undergraduates and postgraduates from Universiti Putra Malaysia participated in a True Experiment based on Pretest-Posttest Control Group procedures. Simple random sampling was used to randomize participants into two treatments (gain and loss) groups and one control group (neutral). All variables were tested for validity and reliability in a pilot study prior to the field data collection. Descriptive analysis, Pearson’s Correlation, Multiple Regression and Independent t-test were employed for data analysis. The result show that valence frames had no significant effect to preventive behaviours. Knowledge moderates the relationship. In the means comparison, gain frame enhances better than loss frame in preventive behaviours. Meanwhile, different level of educational background had no significant effect to preventive behaviours. One significant contribution of the research findings is that it has clarified the role of knowledge in the relationship between valence framing effects and preventive behaviours. A participant with higher knowledge on COVID-19 got influence through positive news frame and they practice proper preventive behaviours while navigating a healthy lifestyle. Meanwhile it is also proven that participants exposed to gain frame practice better protective measures compared with those exposed to loss frame. This research is a pertinent input that could be used to ensure good media framing practice, particularly in identifying which frames work the best in engaging with proper COVID-19 preventive behaviours within public.